Avoiding touching until 60 min—contamination of transdermal estradiol gel after physical contact - Cao, Yi; Zhang, Le; Wei, Jing; Liao, Jingnan (Frontiers in Endocrinology, 2025)
IntroductionThis study aimed to explore the relationship between the timing of physical contact and the level of estradiol contamination in the skin after application of estradiol gel. Estradiol gel is a common medication used in menopausal hormone therapy (MHT) and understanding its potential for contamination is crucial for ensuring patient safety and effective treatment.PurposeThe purpose of this hospital-based case–control study was to determine the correlation between the timing of physical contact and the degree of estradiol contamination following the administration of estradiol gel. This information is vital for advising patients on appropriate precautions to minimize the risk of estradiol transfer to others.MethodsThis study was conducted in the gynecology department of Changsha Hospital for Maternal & Child Health Care Affiliated to Hunan Normal University between 2021 and 2022. The participants included 40 menopausal women aged 40–60 years who required MHT and 40 women who did not use estradiol. The intervention involved physical contact after the administration of estradiol gel, and the main outcome measure was estradiol concentration on the skin. Skin estradiol levels were assessed at 10 min, 30 min, 60 min, and 120 min post-application.ResultsThe results indicated that the estradiol levels in the skin of the estradiol gel group were 205.29 ± 79.33, 193.64 ± 61.17, 99.15 ± 37.34, and 110.83 ± 69.81 at 10 min, 30 min, 60 min, and 120 min, respectively. In contrast, the estradiol content in the skin of the physical contact group was significantly lower, with levels of 65.87 ± 32.75, 59.06 ± 24.99, 7.95 ± 4.89, and 12.09 ± 3.71 at the same time points. Estradiol contamination was detected in all participants in the physical contact group; however, the levels were markedly lower than those in the estradiol gel group. In the estradiol gel group, estradiol levels remained stable within the first 30 min (p >0.05), rapidly decreased at 60 min (p <0.001) and remained stable from 60 min to 120 min (p >0.05). The trend in skin estrogen concentration over time in the physical contact group was consistent with that in the estradiol gel group.ConclusionThe study concludes that physical contact following application of estradiol gel can lead to skin contamination. Therefore, it is recommended that patients avoid skin exposure for at least 60 min after applying estradiol gel and refrain from physical contact with others, especially infants, children, individuals with breast cancer or other sex hormone-dependent tumors, and pets to minimize the risk of estradiol transfer.